An analysis on integrated supply chain management in academic university library - Hye, A. K. Mahbubul (2022)
Supply chain management has been widely used in manufacturing industries and proven by researchers and practitioners as a best practice. It can satisfy stakeholders, increase revenues, and decrease the total costs. However, very few service industries, particularly the academic library, have implemented supply chain management. Several problems related to the academic library supply chain should be addressed, such as how to model the entities and their functions for the general practice of an academic library supply chain, and the linkage among these entities as an integrated model. This research develops an integrated academic library supply chain model, which can be used for the strategic planning of the academic library. It identifies entities and their functions for the academic library supply chain, constructs a conceptual model of the integrated supply chain of the academic library, and analyses the interrelationship among the newly developed model entities. This research used both qualitative and quantitative approaches to achieve the research objectives. The process of identifying the entities and their functions of the academic library supply chain was accomplished by using a theoretical literature review and content analysis techniques. The proposed conceptual supply chain model was developed based on the system thinking method. Eventually, it was validated through the Fuzzy Delphi method, an expert judgment technique. Three conceptual models for the supply chain academic library were successfully developed: The Holistic View of Supply Chain Model for Academic Library, the Material Purchasing Decision Making Model, and the Integrated Academic Library Supply Chain Model. These three models were validated by the academic librarians. This research expands the knowledge of supply chain theory, particularly in the supply chain academic library. It also contributes to the academic library management in planning and formulating a roadmap for the library to increase its quality services for all stakeholders.